What Is the Role of Local Antimicrobial Protection for One-Stage Revision for Peri-Prosthetic Hip Infection? - Carlo Luca Romanò; Luigi Bonomo; Giulio Bonomo; German Viale; Hernán Del Sel; Mohammad Tezval (MDPI AG, 2024)
The aim of this review is to investigate the effective role of local antimicrobial protection for one-stage cemented and cementless hip revision surgery. Twelve studies reporting the results of cemented single-stage procedures with a minimum two-year follow-up were reviewed. When pooling together the data, no infection recurrence was observed on average in 83.3% of the patients (a range of 75.0% to 100%). Only two papers included patients treated without the use of antibiotic-loaded bone cement, with an average infection control of 95.9% in a total of 195 patients. This figure appears to be better than the 80.7% infection control obtained by pooling together all the remaining studies. Concerning cementless one-stage revision, a total of 17 studies, reporting on 521 patients, showed an average of 90.0% (range 56.8% to 100%) no infection recurrence at a minimum two-year follow-up. No comparative study investigated cementless revision with or without local antibacterial protection. The pooled data showed an average infection control of 86.7%, without the application of local antibacterials, compared to 90.1% to 100% with local antimicrobial protection, depending on the technology used. No statistical difference could be found, either considering local antibacterial strategies alone or pooled together. No side effects had been reported by any local antibacterial technique. Local antibacterial protection for one-stage hip revision surgery, although safe and largely performed in the clinical setting, appears to still rely mainly on experts' opinions with no prospective or comparative trial, hence no definitive conclusion can be drawn concerning its effective role in one-stage hip revision surgery.